In vitro Model Systems for Studies Into Retinal Neuroprotection - Zhu, Yu; Cao, Bowen; Tolone, Arianna; Yan, Jie; Christensen, Gustav; Arango-Gonzalez, Blanca; Ueffing, Marius; Paquet-Durand, François (Frontiers in Neuroscience, 2022)
Therapy development for neurodegenerative diseases of the retina constitutes a major unmet medical need, and this may be particularly relevant for inherited diseases of the retina, which are largely untreatable to this day. Therapy development necessitates appropriate models to improve the understanding of the underlying degenerative mechanisms, as well as for the testing and evaluation of novel treatment approaches. This review provides an overview of various in vitro model systems used to study retinal neuroprotection. The in vitro methods and technologies discussed range from primary retinal cell cultures and cell lines, to retinal organoids and organotypic retinal explants, to the cultivation of whole eyeballs. The advantages and disadvantages of these methods are compared and evaluated, also in view of the 3R principles (i.e., the refinement, reduction, and replacement of live animal testing), to identify suitable in vitro alternatives for in vivo experimentation. The article further expands on the use of in vitro models to test and evaluate neuroprotective treatments and to aid the development of retinal drug delivery systems. Among the pharmacological agents tested and characterized in vitro are such that interfere with aberrant cyclic guanosine monophosphate (cGMP) -signaling or such that inhibit the activities of poly (ADP-ribose) polymerase (PARP), histone deacetylases (HDAC), calpain-type proteases, as well as unfolded protein response-related stress. We then introduce nanoparticle-based drug delivery systems and discuss how different in vitro systems may be used to assess their efficacy in the treatment of retinal diseases. The summary provides a brief comparison of available in vitro models and relates their advantages and limitations to the various experimental requirements, for instance, for studies into disease mechanisms, novel treatments, or retinal toxicity. In many cases, combinations of different in vitro models may be required to obtain a comprehensive view of the efficacy of a given retinal neuroprotection approach.